2019
DOI: 10.1103/physrevb.100.205113
|View full text |Cite
|
Sign up to set email alerts
|

Electronic band structure and pinning of Fermi energy to Van Hove singularities in twisted bilayer graphene: A self-consistent approach

Abstract: The emergence of flat bands in twisted bilayer graphene leads to an enhancement of interaction effects, and thus to insulating and superconducting phases at low temperatures, even though the exact mechanism is still widely debated. The position and splitting of the flat bands is also very sensitive to the residual interactions. Moreover, the low energy bands of twisted graphene bilayers show a rich structure of singularities in the density of states, van Hove singularities, which can enhance further the role o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
120
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 69 publications
(131 reference statements)
6
120
2
Order By: Relevance
“…Figure 5 shows that the extra electron fill the flat states and align the Dirac point with the Fermi energy. Small modifications in the electronic band structure as a result of new electrostatic contributions is observed, similarly to other twisted multilayer systems [68][69][70][71].…”
Section: Impact Of Chemical Dopingmentioning
confidence: 60%
“…Figure 5 shows that the extra electron fill the flat states and align the Dirac point with the Fermi energy. Small modifications in the electronic band structure as a result of new electrostatic contributions is observed, similarly to other twisted multilayer systems [68][69][70][71].…”
Section: Impact Of Chemical Dopingmentioning
confidence: 60%
“…van Hove energy. Most important corrections to the van Hove energy ( v ) comes from various interaction effects [67][68][69]. This may not only alter the value of v but also displace the vHS in the k space.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known, however, that long-ranged interactions play an important role in tBLG. Using Hartree theory, several groups [46][47][48][49][50] demonstrated that long-ranged interactions result in significant changes of the electronic structure which depend sensitively on doping and twist angle. In particular, Hartree interactions result in a flattening of the doped bands (in addition to the band flattening induced by twisting) [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%